Risk factors for readmission within one year after acute exacerbations of bronchiectasis in a Chinese tertiary hospital: a retrospective cohort study - Yaxin Fan; Ben Su; Huiyong Zhang; Xiaoyu Yang; Zhengyi Zhang; Shaoyan Zhang; Shunxian Zhang; Dingzhong Wu; Peiyong Zheng; Zhenhui Lu; Lei Qiu (BMC Pulmonary Medicine)
Abstract Background Frequent exacerbations of bronchiectasis lead to poor quality of life, impaired lung function, and higher mortality rates. This study aims to evaluate the risk factors associated with readmission within one year due to acute exacerbation of bronchiectasis (AEB). Methods A retrospective cohort study was performed on 260 patients with bronchiectasis who were hospitalized in the respiratory and critical care department of a tertiary hospital in China. Univariate and multivariate Cox analyses were used to evaluate the risk factors for readmission within one year. Results Readmission within one year was found in 44.6% of 260 patients hospitalized with acute exacerbation of bronchiectasis. The risk factors associated with readmission included age over 65 years (HR = 3.66; 95% CI: 2.30 to 5.85), BMI < 18.5 kg/m2 (HR = 1.71; 95% CI: 1.16 to 2.51), respiratory intensive care unit (RICU) stay during admission (HR = 2.06, 95% CI: 1.16–3.67), involvement of 3 or more lobes on chest high-resolution computed tomography (HRCT) (HR = 1.85; 95% CI, 1.22 to 2.80), chronic Pseudomonas aeruginosa (PA) colonization (HR = 2.29; 95% CI: 1.54 to 3.38), and positive sputum culture results within 24 h after admission (HR = 1.93; 95% CI: 1.27 to 2.94). Long-term oral antibiotics use after discharge was associated with decreased hazard of readmission (HR = 0.34; 95% CI: 0.20 to 0.59). Conclusions Patients with bronchiectasis have a high rate of readmission, which is linked to varieties of risk factors, and identifying these risk factors is importance for effectively managing patients with bronchiectasis.